(untitled) (ELEKTRIKA- Journal of Electrical Engineering, 2021)
MEMS-based micro-electro-discharge machining (M3EDM) is a batch microfabrication technique that utilizes planar-electrode actuators fabricated directly on the work material. Electrostatically driving the electrode-actuator device, previously enabled with copper-based designs, using an applied EDM voltage enables micromachining of electrode patterns into any electrically conductive material. This paper presents an alternative device based on nickel with its higher thermomechanical resistance, aiming to achieve greater uniformity and stability of the process toward its application to micromanufacturing. The developed nickel-based device and its M3EDM process is used to pattern cantilever-like MEMS contact switches as a preliminary application test, demonstrating the process with the intended effects. The outcome is analyzed to suggest a need for improvement, which is addressed through a modified approach to the M3EDM fabrication of application devices showing a promising result. The study encourages further optimizations of the technology, which are evaluated and discussed as well.